Research Patterns of Suicide Prevention Based on Sustainable Social Development - Anisa Siti Nurjanah (CERDAS AKADEMIKA NUSANTARA, 2026)
Suicide prevention was a global mental health issue that was closely related to sustainable social development. The increasing attention to this issue encouraged the growth of interdisciplinary scientific publications, but it also led to potential fragmentation of knowledge. This study aimed to map the development of research on suicide ideation prevention within the perspective of sustainable social development using bibliometric analysis. Data were obtained from the Scopus database using keywords related to suicidal ideation, suicide prevention, community, social development, and sustainable development. A total of 4,424 English-language journal articles published between 1958 and 2025 were analyzed using VOSviewer software. Bibliometric analysis was conducted to identify publication trends, country contributions, and author productivity. The results showed that publications on suicide prevention within the context of sustainable social development increased significantly since the mid-1990s, with publication peaks occurring in 2024 and 2025. The United States became the largest contributor in terms of publications and citations, followed by Australia, Canada, and the United Kingdom. In addition, the author analysis revealed several researchers who occupied central positions in scientific collaboration networks and played important roles in advancing suicide prevention research. These findings confirmed that suicide ideation prevention was increasingly positioned as an integral part of the sustainable social development agenda and required more inclusive global research collaboration.